2022
DOI: 10.1177/09646639221118654
|View full text |Cite
|
Sign up to set email alerts
|

Silence and Voice in Oral Hearings: Spatial, Temporal, and Relational Conditions for Communication in Asylum and Compulsory Care Hearings

Abstract: The legal right to be heard by a judge is an important human right. However, what happens if a claimant does not meet the requirements of legal communication when given the opportunity to be heard in court? In this article, I address this question by exploring how temporal, spatial, and relational conditions encourage or silence vulnerable claimants’ voices in asylum hearings and compulsory psychiatric care hearings in Swedish administrative courts. In addition, I analyze the multiple functions orality has whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Rowden (2018) discusses how remote court hearings deteriorate the quality of the proceedings as the ceremonial aspects are lost, and Hambly and Gill (2020) make a similar remark regarding the negative consequences of rushed hearings in court. Johannesson (2022), in turn, demonstrates that the quality of the communication between claimants and judges is partly determined by what kinds of ceremonies are performed during court hearings. In addition, political scientists have demonstrated that when people start to mistrust the quality and fairness of state institutions, a self-fulfilling spiral of mistrust begins that risks eroding the quality of government and the effectiveness of the welfare state and the democratic system (Rothstein & Stolle, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Rowden (2018) discusses how remote court hearings deteriorate the quality of the proceedings as the ceremonial aspects are lost, and Hambly and Gill (2020) make a similar remark regarding the negative consequences of rushed hearings in court. Johannesson (2022), in turn, demonstrates that the quality of the communication between claimants and judges is partly determined by what kinds of ceremonies are performed during court hearings. In addition, political scientists have demonstrated that when people start to mistrust the quality and fairness of state institutions, a self-fulfilling spiral of mistrust begins that risks eroding the quality of government and the effectiveness of the welfare state and the democratic system (Rothstein & Stolle, 2008).…”
Section: Discussionmentioning
confidence: 99%